S100 protein and interleukin biomarkers among COVID-19 subjects with and without pneumonia: a systematic review and meta-analysis - Koyou, Haily Liduin; Ramachandran, Vasudevan; Salleh, Mohd Nazil; Wan Sulaiman, Wan Aliaa; Mohamed, Mohd Hazmi; Mohd Badrin, Mohd Jaamia Qaadir; Jelemie, Caroline Satu (Frontiers Media SA, 2026)
Background: The global spread of COVID-19, caused by SARS-CoV-2, has resulted in a wide spectrum of clinical manifestations, ranging from asymptomatic cases to severe complications, such as pneumonia, acute respiratory distress syndrome (ARDS), and multiple organ failure. Identifying effective biomarkers is essential for predicting disease severity and improving patient management. Objectives: This meta-analysis aims to assess the significance of S100 proteins (S100A4, S100A8, S100A9, S100A12, S100B, S100P) and interleukins (IL) (IL-6, IL-8, IL-10, IL-17, IL-1β) in COVID-19 patients, comparing those with and without pneumonia or organ failure. Methods: A systematic literature search was conducted on different databases, yielding 47 relevant studies published between 2020 and 2024. Data on the prevalence of IL and S100 protein levels were extracted and analyzed using pooled standardized mean differences (SMD) and heterogeneity (I2) to evaluate their associations with disease severity. Results: IL-6 and IL-10 levels were significantly elevated in COVID-19 patients suffering from pneumonia or organ failure. IL-6 levels were notably higher in pneumonia patients compared to those without (SMD = 0.34 [95% CI: 0.17, 0.52], I2 = 29%). Similarly, elevated S100B levels were observed in severe cases (SMD = 0.51 [95% CI: 0.19, 0.83], I2 = 0%). While IL-10 levels showed high variability (I2 = 90%), they remained consistently linked with worse outcomes. Conclusion: This meta-analysis underscores the potential of IL-6, IL-10, and S100 proteins as important biomarkers in evaluating COVID-19 severity, offering valuable insights to help clinical management.